The Theatrical Life of Documents - Martin, Carol (Peripeti, 2014)
The notion that documents provide incontrovertible evidence has long been in question. Yet documents, in both their material and digital forms, are still well respected and are used as sources of information with consequences for the creation of meaning in historical accounts, in legal procedures, and on theatre stages. The theatrical life of documents may or may not contain anything real, in the sense of actual, physical, factual, or material. What is the document, what is its province, and what kinds of meanings does the way in which it is staged produce? I will address these questions in relation to three international performances: Double Edge Theatre’s The Grand Parade directed by Stacy Klein (2013), The Year I Was Born (2010), and The Pixelated Revolution (2011).